The Other (Muscarinic) Acetylcholine Receptors in Sympathetic Ganglia: Actions and Mechanisms - Brown, D.A. (Нейрофизиология, 2013)
Acetylcholine released from preganglionic sympathetic fibers can activate two types of
acetylcholine receptors in sympathetic neurons, nicotinic and muscarinic. The former
are ligand-gated ion channels responsible for direct synaptic transmission; the latter are
G protein-coupled receptorsthat mediate variousindirect modulatory effects. Most mammalian
sympathetic neurons express three muscarinic receptor subtypes, M1, M2, and M4; some also
express M3 receptors. Activation of M1 receptors stimulates the G protein Gq and causes a
slow postsynaptic depolarization and an increase in the excitability, ultimately leading to an
asynchronous action potential discharge, which can “break through” the nicotinic ganglion
block. This is largely mediated by closure of voltage-gated K+ channels (the M channels)
composed of Kv7.2 and Kv7.3 subunits and results from hydrolysis and depletion of
membrane phosphatidylinositol-4,5-bisphosphate. Activation of M2 receptors hyperpolarizes
and inhibits the postsynaptic neuron by opening G protein-gated inwardly-rectifying Kir K+
channels via the G protein Gi. M4 receptors inhibit N-type (CaV(2)) calcium channels via
the G protein Go. In the postganglionic neuron somata, this enhances the excitability by
reducing calcium-dependent potassium currents. Conversely, in postganglionic processes
and axon terminals, CaV(2)-mediated inhibition reduces norepinephrine release and inhibits
postganglionic transmission. Different muscarinic receptors may be anatomically segregated
with their cognate G proteins and (in some cases) ion channels in signalling microdomains. Ацетилхолін, котрий вивільнюється з прегангліонарних волокон, може активувати в симпатичних гангліях ацетилхолінові рецептори двох типів – нікотинові та мускаринові.
Перші з них мають лігандкеровані іонні канали, відповідальні за пряму синаптичну передачу; другі ж є рецепторами, зв’язаними з G-протеїнами, та опосередковують різні непрямі модуляторні ефекти. У більшості симпатичних
нейронів ссавців експресуються мускаринові рецептори
трьох підтипів – M1, M2 та M4; у деяких також експресуються рецептори підтипу M3. Активація рецепторів M1 зумовлює стимуляцію G-протеїну Gq; це викликає повільну
деполяризацію постсинаптичного нейрона та підвищення
його збудливості, що, кінець кінцем, призводить до генерації асинхронного розряду потенціалів дії. Така генерація може проривати „нікотинове” блокування ганглія. Цей
ефект в основному опосередковується закриванням потенціалкерованих калієвих М-каналів, що складаються із субодиниць Kv7.2 та Kv7.3, завдяки гідролізу та вичерпанню
запасів мембранного фосфатидилінозитол-4,5-бісфосфату.
Активація рецепторів M2 призводить до гіперполяризації та гальмування постсинаптичного нейрона в результаті відкривання G-протеїнкерованих калієвих каналів внутрішнього випрямлення Kir, опосередкованого G-протеїном Gi.
Рецептори M4 гальмують кальцієві канали N-типу CaV(2);
ефект опосередковується G-протеїном Go. У сомах постгангліонарних нейронів це зумовлює збільшення збудливості (через зменшення кальційзалежних калієвих струмів).
У відростках постгангліонарних нейронів та аксонних терміналях, навпаки, CaV(2)-опосередковане гальмуванням
зменшує вивільнення норепінефрину та пригнічує постгангліонарну передачу. Різні мускаринові рецептори можуть
бути анатомічно відокремленими одні від інших завдяки локалізації їх споріднених G-протеїнів та (у деяких випадках)
іонних каналів у різних сигнальних мікродоменах.